Anticoagulation Control with Daily Low‐Dose Vitamin K to Reduce Clinically Adverse Outcomes and International Normalized Ratio Variability: A Systematic Review and Meta‐Analysis. Issue 11 (6th June 2013) - Lam, Jason; Schulman, Sam; Witt, Daniel M.; Vandvik, Per Olav; Qayyum, Fareeha; Holbrook, Anne M.
Abstract : Study Objectives: Difficulties managing warfarin therapy have led to speculation that daily supplementation with a low dose of vitamin K might improve anticoagulation control and clinical outcomes. Thus we sought to review the available medical literature systematically examining the effectiveness of low‐dose vitamin K supplementation for the reduction of clinically relevant adverse events due to vitamin K antagonist (VKA) use and for stabilization of the international normalized ratio (INR). Design: We searched the Medline and Embase databases, the Cochrane Library, International Pharmaceutical Abstracts, and the U.S. National Institutes of Health clinical trials registry for randomized controlled trials of vitamin K supplementation versus placebo in patients receiving a VKA. We evaluated the outcomes of hemorrhage, thromboembolic events, and percentage of time in therapeutic range (TTR) of INRs by using the Grading of Recommendations Assessment, Development and Evaluation system for rating quality of evidence in the abstracted studies. Setting: All randomized controlled trials studies published between 1970 and August 2012 which fitted our search strategy. Patients: Patients over the age of 18 years on VKA therapy. Results: Of the 624 studies we identified and screened, three studies (626 patients) were included in the meta‐analysis. Most of the patients had a satisfactory TTR at baseline. We found low‐quality evidence—downgraded for imprecision and risk of bias (i.e., limitation in study design and/or execution)—of no effect of vitamin K use (100 to 200 μg) on hemorrhagic events (relative risk [RR] 3.2, 95% confidence interval [CI] 0.2–64.2) and thromboembolic events (RR 2.2, 95% CI 0.1–47.5) and a significant but clinically unimportant effect on TTR with an absolute increase of 3.5% (95% CI 1.1–6.0). Conclusion: This meta‐analysis, despite the few studies and overall low quality, suggests no beneficial role of low‐dose (100 to 200 μg) vitamin K supplementation on the reduction of clinically relevant adverse events in patients taking VKAs, despite a small improvement of the TTR. Data were insufficient, however, from patients with unstable INRs.